2017
DOI: 10.5811/westjem.2016.10.31234
|View full text |Cite
|
Sign up to set email alerts
|

Can Emergency Medicine Residents Predict Cost of Diagnostic Testing?

Abstract: IntroductionDiagnostic testing represents a significant portion of healthcare spending, and cost should be considered when ordering such tests. Needless and excessive spending may occur without an appreciation of the impact on the larger healthcare system. Knowledge regarding the cost of diagnostic testing among emergency medicine (EM) residents has not previously been studied.MethodsA survey was administered to 20 EM residents from a single ACGME-accredited three-year EM residency program, asking for an estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…A recent study by Tainter et al demonstrated poor insight by ED residents regarding costs, which increases the economic burden on healthcare systems. 22 Although addressing this issue is not currently applicable to our setting where the cost of a test is not visible to the ordering physician, making costs visible can be easily adopted in ED settings to control the cost of care. Importantly, continuous training and education about the immeasurable damage of the inappropriate use of antibiotics in the community should be prioritized given the increasing rates of antimicrobial resistance worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Tainter et al demonstrated poor insight by ED residents regarding costs, which increases the economic burden on healthcare systems. 22 Although addressing this issue is not currently applicable to our setting where the cost of a test is not visible to the ordering physician, making costs visible can be easily adopted in ED settings to control the cost of care. Importantly, continuous training and education about the immeasurable damage of the inappropriate use of antibiotics in the community should be prioritized given the increasing rates of antimicrobial resistance worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have shown that residents in departments other than ED including paediatrics and internal medicine lack the knowledge about the cost of many tests, and awareness may therefore have a role in improving practice . A recent pilot study by Tainter et al compared responses from residents in the ED demonstrating a very poor insight about costs burdening patients and healthcare plans . Although this might not be applicable to our setting where the cost of a test is visible to the ordering physician, this approach would be useful to adopt in ED settings and healthcare settings in general to control cost of care and unnecessary test utilisation.…”
Section: Discussionmentioning
confidence: 99%
“…In today's access-blocked emergency departments (EDs), many tests are ordered by nurses or trainees to expedite patient care. 3,13 These users often have limited experience interpreting test results, scant training in testing theory, and an exaggerated sense of test utility. 13 Our objective is to describe a minimum knowledge set for every clinician who orders tests in the ED, and propose a five-step cognitive tool to apply before ordering tests (Table 1).…”
Section: Introductionmentioning
confidence: 99%